Ömer Fuâdî'nin Türkçe tasavvuf risaleleri - Demirel, İsmail (My University, 2018)
Pir Şa’bân-ı Velî (ö. 976/ 1569) tarafından tesis edilen Şa’bânîlik, İslâm dünyasının en yaygın tarikatlarından biri olan Halvetiyye’nin önemli kollarındandır. Şa’bânîlik tarihinde, Ömer Fuâdî (ö. 1046/ 1636), başta Şa’bânîlik ve Pir Şa’bân-ı Velî olmak üzere, kendisinden önceki postnişinlerin tanınması, tarikatın âdâb ve erkân sistematiğinin kayda geçirilmesi, tarikat usûlünün aktarılabilir bir somutluk içerisinde tayin edilmesi hususunda önemli bir yer tutar. Şa’bân-ı Velî’den sonra Kastamonu âsitânesinin beşinci postnişini olan Fuâdî, çoğunluğu Türkçe kırkı aşkın eser kaleme almıştır. Üç bölümden oluşan tezde Ömer Fuâdî’nin hayatı, tarikatı, silsilesi, mürşidleri, müridleri, tarikat faaliyetleri incelenmiş; Fuâdî’nin on dört risâlesinin çevrimyazısı yapılmış, bu risaleler eşliğinde tarikat anlayışı ortaya konmaya çalışılmıştır. Bu minvalde müellifin mürid, mürşid, zikir, halvet, devran, âdâb gibi meselelere bakışı temel tasavvuf kaynakları ışığında ele alınmıştır.

Halvetiyyah is one of the most common sufi orders of the Islamic world. Shabaniyyah established by Pir Shabân-ı Velî (d. 976/ 1569) is an important branch of Halvetiyyah.In the history of tariqah Shabaniyyah, Omar Fuâdî (d. 1046/ 1636) has an important place on the following issues: recognition of the postnishins (sheikhs) before him, especially Pir Shaban-ı Velî and the silsile of Shabaniyyah, the recording of the systematic moral and rules of the sufi order, determination of religious order proccess in a transferable conformation. After Shaban-ı Velî, Fuâdî, becoming the fifth postnishins of main shrine (âsitâne) in Kastamonu, wrote a number of works, most of which are in Turkish.In the thesis composed of three parts, the life, sufi order, folklore, sufi guides (murshid), discriples (murid) and sects activities of Omar Fuâdî were studied; the translation of Fuâdî’s fourteen rites has been made, and attempts have been made to reveal the understanding of sects along with these treatises. In this way, the author’s view on issues such as murid, murshid, zikir, halvet, devran, âdab was taken up in the light of basic sources of mysticism.
Keywords: Âdâb Halvatiyya; Alevilik; Biography; Biyografi; Halvatiyya; Halvetilik; Halvetîlik; History; Islamic etiquette; Islamic religious; IstIslamic religious; İslam adâbı; İslam dini; İslam dini - Tarikatlar; Khalwatiyah; Khalwatīyah; Mistik tedaviler; Mystical treatments; Mystical Treatments (Âdâb); Omar Fuâdî; Orders; Ömer Fuâdî; Pir Shaban-i Velî; Pir Şa’bân-ı Velî; Pir Şaban-ı Veli, d. 1569; Pir Şaban-ıFuâdî, Veli, d. 1569; Shabaniyya; Sufism; Şa’bânîlik; Şabaniyye; Tarih; Turkey; Türkiye